Strategi Pelayanan Misi Dimasa Pandemi Coronavirus Disease 2019 - Adieli Waruwu; Samuel Purdaryanto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
At the end of 2019, the whole world and Indonesia were shocked by the emergence of the new coronavirus disease 2019. It has been more than a year since this disaster struck. The number of victims around the world has reached more than one hundred million with the death toll of more than two million people. Various efforts have been made to prevent the spread of this virus, one of which is social restrictions so that it has an impact in various areas of human life. One of the impacts is the missionary service which usually carries out social and face-to-face interactions. By using qualitative research methods with a literature review approach, observation, and interviews and then describing, this study will provide answers and solutions for mission service strategies during the Covid19 pandemic. The results of this study found answers to mission services online or online. By utilizing internet networks and social media, the gospel can still be preached despite social restrictions. Facebook, YouTube, Instagram, and Tiktok are some social media applications that can be used for mission services during the Covid-19 pandemic, through these applications this news can be presented in the form of writing, audio, and video which are shared via social media. This strategy, with its strengths and weaknesses, provides a great opportunity to continue working on the Great Commission of the Lord Jesus during the Covid-19 pandemic.